Preferences for Attachment Devices for Individuals with Lower-Limb Loss: A Discrete-Choice Study to Inform Regulatory Decisions - Leslie Wilson; Matthew Garibaldi; Ruben Vargas; Molly Timmerman (MDM Policy & Practice)
Objective. The patient’s perspective in shared decision making has expanded to regulatory decision making for medical devices under the Food and Drug Administration’s Patient Preference Initiative. Methods. Using choice-based conjoint (CBC) procedures, a discrete-choice experiment measure describing the risks and benefits of osseointegration was designed and used in a preference study among 188 adults with lower-limb loss. Our measure included 8 attributes of 1) risks: chance of infection, complete device failure rate, time without prosthesis, activity limitations, and 2) benefits: avoidance of socket problems, limb perception, improved motion with less fatigue, and chance of limiting daily pain, with 3 to 4 levels each. We used a random, full-profile, balanced-overlap design in which 18 CBC conjoint pairs, sociodemographic, and clinical questions were completed. The analysis included random parameters logit with 1,000 Halton draws and latent class. Results. The least important levels, when compared with their respective attribute baseline level, were for avoiding the highest chance (50%) of serious infection (β = −1.32, P < 0.001), highest chance (40%) of complete device failure (β = −0.96, P < 0.001), and longest (9 mo) time without prosthesis (β = −1.12, P < 0.001). The most preferred levels, when compared with their respective attribute baseline level, were to eliminate daily pain (β = 0.87, P < 0.001; β = 0.62, P < 0.001). The preference for avoiding current osseointegration infection risk (10%) was much lower (β = 0.51, P < 0.001), showing that preferences to avoid the actual infection risk are offset by osseointegrations benefits. Latent class analysis showed 2 distinct classes with some risk averse and some with more balanced preferences. Conclusions. The strongest preferences were seen for attributes avoiding complications; however, individuals demonstrated a willingness to make risk–benefit tradeoffs at current risk levels. These findings can guide future regulatory prosthetic decisions and allow better shared decision making to decrease prosthetic abandonment. Highlights Importance shown to avoid the actual infection risk of osseointegration can be offset by the individual’s importance for the benefits of osseointegration to avoid pain and socket problems and to have rapid device snap on. Individuals also showed they are willing to trade the actual osseointegration device failure rate risks for the likely benefits of osseointegration. Individuals strongly preferred avoiding time without the use of a prosthetic for the time it takes to undergo and recover from the osseointegration procedure, informing the debate for favoring a faster procedure and recovery time if it is safe. However, these preferences were still in the tradeoff range for the benefits of osseointegration. Individuals showed the strongest importance for a potential benefit of osseointegration to reduce the presence of daily pain, which is a likely benefit of the osseointegration procedure, especially when accompanied by targeted muscle reinnervation. We showed considerable heterogeneity across patient preferences, with one group showing a strong importance for avoiding risks but also importance for some benefits of osseointegration and a larger group who showed a more moderate importance across both risks and benefits.